EFFECT OF ANTHROPOMETRIC MEASUREMENTS AND PERSONAL DATA PARAMETERS ON BENIGN PROSTATIC HYPERPLASIA AND CARCINOMA PROSTATE - Naz, Zehra; Anjum, Saadia (Journal of Ayub Medical College Abbottabad, 2010)
Background: With advancing age the chances of benign prostatic hyperplasia (BPH) and carcinoma prostate (CaP) increases. Although previous studies on physical parameters and personal data parameters have shown the positive associations between BMI, family history, and marital status but they have not seen the effect of occupation and socioeconomic status on BPH and CaP. The objective of the present study was to see the effects of anthropometric measurements and personal history parameters on BPH and CaP in our community. Methods: Ninety-three willing subjects from the outpatient department of Sindh Institute of Urology and Transplant (SIUT) were selected for the study. Height and weight were measured, BMI calculated and personal data information, i.e., occupation, marital status, smoking history, family history and socioeconomic history were recorded. Data were analysed for association of various parameters with BPH and CaP. Results: Significant association between weight, BMI and skilled labourers was found when normal were compared with BPH cases. Conclusion: No significant association between other parameters and BPH, CaP cases was found, except weight, BMI and skilled labour. Body weight should be managed well as it can lead to both cardiovascular as well as prostatic diseases. Keywords: Body mass index, Benign Prostatic Hyperplasia, CaP, Carcinoma prostate